Artificial intelligence literacy and adoption among basic education teachers - Trixie E. Cubillas; Neunna Vinzie D Dela Cruz; Gwyneth Queen F Galvadores; Jileen May B Olivares; Ariel U. Cubillas (Institute of Advanced Engineering and Science, 2026)
Despite growing interest in artificial intelligence (AI) integration, a gap in AI literacy and adoption among teachers limits the benefits of AI-enhanced learning and widens the digital divide. This study explored AI literacy and adoption among basic education teachers in Butuan City, Philippines, using the technological pedagogical content knowledge (TPACK) framework and social cognitive theory (SCT). It examined factors influencing readiness to integrate AI tools into teaching. Using a quantitative descriptive-causal design, data from 243 randomly selected teachers were analyzed through structural equation modeling (SEM) with the adopted research instruments. Results show that AI literacy and positive affective-cognitive variables strongly predict AI adoption, with behavioral intention (BI) mediating the link between self-esteem (SE) and AI literacy. Findings underscore the need for targeted professional development and institutional support to bridge the AI literacy gap and ensure the responsible and effective integration of AI in primary education.